Characterization of mineral composition of leaves and flowers of wild-growing Sambucus nigra - Qazimi Bujar; Stafilov Trajče; Andonovska Katerina Bačeva; Tašev Krste; Geskovski Nikola; Dragusha Shpend; Koraqi Hyrije; Ejupi Valon (Acta Pharmaceutica)
The objective of this study was to determine the mineral content in the leaves and flowers of wild-grown Sambucus nigra collected from eleven different locations in Kosovo. The samples were digested in a microwave system using the wet digestion method. The minerals were determined by the application of inductively coupled plasma-atomic emission spectrometry (ICP-AES) and inductively coupled plasma-mass spectrometry (ICP-MS). A total of 31 elements were determined, 15 elements by the ICP-AES method (Al, B, Ba, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, P, Sr, V, and Zn) and 16 elements by the ICP-MS method (Ag, As, Be, Bi, Cd, Co, Cs, Ga, Hg, In, Li, Ni, Pb, Rb, Tl, and U). The leaves of S. nigra show a higher content of minerals compared to the flowers, except for the flower of the sample SN-FL10, which is characterized by a high concentration of Fe, Al, Pb, Be, and Tl. The concentration of heavy metals and toxic elements (Pb, Cd, and Hg) was within the permissible concentrations according to Eur. Ph.